2020
DOI: 10.1155/2020/9289651
|View full text |Cite
|
Sign up to set email alerts
|

Prevalidation of an ELISA for Detection of a New Clinical Entity: Leishmania donovani-Induced Cutaneous Leishmaniasis

Abstract: Human leishmaniasis which is considered a neglected tropical parasitic disease presents in three main clinical forms (i.e., cutaneous leishmaniasis (CL), mucocutaneous leishmaniasis (MCL), and visceral leishmaniasis (VL)) that are mainly determined by its causative species. Leishmania donovani, the most virulent and visceralizing parasite, is increasingly reported to cause CL in many countries in the world. Although CL is generally not considered to evoke a humoral immune response except for a nonrobust and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…ELISA was carried out using a previously optimized protocol [ 20 , 26 , 27 ]. A ninety-six- (96-) well ELISA plate (Sterilin or Greiner) was coated with 100 μ l (containing at least 1 μ g protein) of crude protein extract and incubated overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…ELISA was carried out using a previously optimized protocol [ 20 , 26 , 27 ]. A ninety-six- (96-) well ELISA plate (Sterilin or Greiner) was coated with 100 μ l (containing at least 1 μ g protein) of crude protein extract and incubated overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Another successful approach has been the use of crude antigens derived from amastigotes of local Leishmania strains [ 88 ]. Seroprevalence studies by Siriwardana et al, 2018, and Deepachandi et al, 2020 [ 90 , 91 ], demonstrated that in-house ELISA assays with soluble crude Leishmania antigens (SLAs) can identify active CL infections, with a sensitivity level of 82.0%. An indirect ELISA assay with SLAs developed by Piyasiri et al, in 2022 [ 92 ], showed high performance, with a sensitivity of 98% and specificity of 90.3%.…”
Section: Immunological Techniquesmentioning
confidence: 99%